Pendampingan Orangtua Dalam Penggunaan Media Digital Edukatif Oleh Anak Usia Dini Di Lingkungan Rumah - Shinta Alfianti; Esya Anesty Mashudi (Fakultas Tarbiyah IIQ Jakarta, 2026)
This study aims to describe the role of parents in assisting early childhood in using educational digital media at home. The study applies a descriptive qualitative approach with a single case study design. The subject is one parent with a young child. Data were collected through in depth interviews and limited observation of the child’s behavior during digital media use. The findings show parental assistance is situational and depends on time availability, with the mother acting as the primary companion. Parents focus more on controlling content than regulating usage duration. The child started using digital devices at the age of three without clear usage guidelines, except restrictions during mealtime and sleep time. Digital media use supports language development through children’s activity videos and English songs. The main challenges include difficulty limiting screen time and reduced supervision when parents are busy working. This study highlights the importance of consistent parental assistance in the use of educational digital media by young children at home.